Constitutional Court Decision on the Age Requirement for Presidential and Vice-Presidential Candidates: Legal Implications and Public Response - Nabila Fauziyyah; Ahmad Ahmad.; Melisa Susanti; Gamal Abdul Nasir; Fakhri Aldifha Kurnia (Universitas Muhammadiyah Tangerang, 2023)
The Constitutional Court Decision Number 90/PUU-XXI/2023, which changed the age limit for presidential and vice-presidential candidates to a minimum of 40 years or having experience in a public office through elections, has sparked controversy in society. This study aims to analyze the role, duties, and position of the Constitutional Court in Indonesia's state administration system, examine judicial independence in this decision, and explore the perspectives of society, politicians, and academics on the legal and social implications of this change. This research employs a qualitative approach with normative juridical analysis based on legal rulings and related literature. The findings indicate that the independence of Constitutional Court judges is in question due to allegations of conflicts of interest that may undermine public trust. Furthermore, this decision affects national political dynamics and public participation in elections. This study provides a critical perspective on the role of the Constitutional Court in upholding democratic principles and the rule of law in Indonesia